Detection of Mycobacterium Tuberculosis in Extrapulmonary Specimens and Drug Sensitivity Pattern in a Tertiary Level Chest Disease Hospital of Bangladesh - Karim, Md Ziaul; Khan, Mohammad Ashik Imran; Banu, Farzana; Shakil, Md Zahirul Islam; Hossain Bhuiyan, Golam Sarwar Liaquat; Aziz, Md Zakaria Al (Journal of Medicine, 2025)
Background: Extra-pulmonary tuberculosis (EPTB) is a growing public health concern, and data on drug resistance in EPTB are limited. Objective: To detect Mycobacterium Tuberculosis in extrapulmonary specimens and to find out identity the pattern of drug sensitivity among extrapulmonary specimens Methods: This cross-sectional study was conducted at the NTRL (National Tuberculosis Reference Laboratory) of the National Institute of Diseases of Chest and Hospital (NIDCH), Bangladesh, from January 2024 to December 2024. This study included 100 patients suspected of suffering from extrapulmonary Mycobacterium Tuberculosis infection. Clinical specimens were obtained from these extrapulmonary sites and were subjected to the GeneXpert test to detect the presence of Mycobacterium TB. Drug sensitivity patterns were tested in the samples that yielded positive results. Results:The Mean age of the patients was 39.25 ± 17.99 years. Most of the patients were 21 – 40 years old.The majority of the patients were male (64.0%).The male-to-female ratio was 1.78:1.The most common extrapulmonary sample tested was pleural fluid. Mycobacterium Tuberculosis was detected in 28.0% of the samples. Extrapulmonary Mycobacterium tuberculosis was predominant among the younger patients. The mean age of patients with EPTB was significantly lower than that of patients without EPTB (29.53 ± 16.27 vs 43.08 ± 17.27; p £0.001). Sensitivity to first and second-line anti-tubercular drugs was evaluated in the extrapulmonary specimens that tested positive. Both first-line anti-tubercular drugs (Isoniazid) and second-line anti-tubercular drugs (Aminoglycosides, Kanamycin, fluoroquinolones, and Ethionamide) were found to be sensitive in 85.7% of cases and resistant in 14.3% of cases respectively. Conclusion: EPTB remains a significant health problem, particularly affecting male and young men with a substantial proportion demonstrating drug resistance. J MEDICINE 2025; 26(2): 89-93